A review of solar chimney for natural ventilation of residential and non-residential buildings. (August 2022) - Maghrabie, Hussein M.; Abdelkareem, Mohammad Ali; Elsaid, Khaled; Sayed, Enas Taha; Radwan, Ali; Rezk, Hegazy; Wilberforce, Tabbi; Abo-Khalil, Ahmed G.; Olabi, A.G.
Highlights: An overview of the operation and performance of the solar chimney were introduced. Potential design and operating parameters affecting the SC was discussed. Natural ventilation in solar chimney was elaborated. Abstract: The requirement for passive cooling strategies in buildings has great attention in almost all countries, where hot temperatures are predominant throughout the year. The ventilation process is a crucial necessity for a healthy lifestyle and its significance is additionally highlighted through the contemporary universal outbreak of Covid-19. One of the promising applications for cooling residential buildings is the solar chimney (SC) that is particularly convenient for hot and humid climates. The solar chimney is a natural draught passive method that utilizes available solar energy to build up the stack pressure. The solar chimney participates in elevating the cooling and heating efficiency of residential/non-residential spaces. The present article introduces an overview of the operation and performance of the SC. Studying the potential design and operating parameters influencing the SC performance for natural ventilation (NV) compared to the electrical high-energy technologies to sustain the acceptable indoor climatic conditions is important. As well, the natural ventilation for harsh climate conditions using SC only is not applicable so the enhanced solar ventilation systems are studied. Combined enhanced cooling/heating energy systems based on the solar chimney are considered as an effective strategy towards low-energy consuming buildings.